siRNA Transfection and EMSA Analyses on Freshly Isolated Human Villous Cytotrophoblasts. - LOKOSSOU, GATIEN; Toufaily, Chirine; Vargas, Amandine; Barbeau, Benoit (My University, 2016)
Human primary villous cytotrophoblasts are a very useful source of primary cells to study placental functions and regulatory mechanisms, and to comprehend diseases related to pregnancy. In this protocol, human primary villous cytotrophoblasts freshly isolated from placentas through a standard DNase/trypsin protocol are microporated with small interfering RNA (siRNA). This approach provided greater efficiency for siRNA transfection when compared to a lipofection-based method. Transfected cells can subsequently be analyzed by standard Western blot within a time frame of 3-4 days post-transfection. In addition, using cultured primary villous cytotrophoblasts, Electrophoretic Mobility Shift Assay (EMSA) analysis was optimized and performed on extracts from days 1 to 4. The use of these cultured primary cells and the protocol described allow for an evaluation of the implication of specific genes and transcription factors in the process of villous cytotrophoblast differentiation into a syncytiotrophoblast-like cell layer. However, the limited time span allowable in culture precludes the use of methods requiring more time, such as generation of a stable cell population. Therefore testing of this cell population requires highly optimized gene transfer protocols.
Keywords: Cytotrophoblast; siRNA; transfection; EMSA